SIMULASI BEBAN RANGKA PADA MESIN PENGGILING SEKAM PADI MENGGUNAKAN PERANGKAT LUNAK - Muhammad Alfarhan Ficki; Kardiman Kardiman; Najmudin Fauji (ROTOR, 2022)
One of the main components in the rice husk grinding machine is the frame. The frame is the most important fundamental part, especially for use in machinery, because the function of the frame is as a support for the components themselves, and is able to withstand axial, normal and moment forces to maintain stability in the machine. The strength of the frame depends on the shape or type of construction which is able to withstand torsional loading from the engine and also withstand the shock that is given when the engine moves. So the purpose of this study is to find out how to simulate the loading of the frame on a rice husk grinding machine using SolidWorks software, and to know the comparison of theoretical calculations and simulations for 3 material variations on the frame of a rice husk grinding machine in a static state. The method used is the Finite Element Method (MEH), MEH with software can determine the loading points. From this test, researchers can find out which points have a minimum load, a medium load, and a maximum load. The results of the analysis provide the safety value of original and processed materials, changes in materials can be concluded which material is more ideal. The results of this study are that among AISI 1010, ASTM A36, and AISI 1045 materials, the best material is AISI 1045 material because it has the greatest safety factor value of 12.15.